A cross-sectional study of Salmonella in pre-slaughter pigs in a production compartment of northern Thailand - S. Dorn-in (2018)
A cross-sectional study was conducted to determine the prevalence of Salmonella and to associate management factors in fattening pigs in a production compartment of northern Thailand. A total of 194 fecal samples and 166 environmental samples were collected from 22 fattening pig herds for isolation and identification of Salmonella. An additional 427 serum samples were collected from the same herds to determine Salmonella antibodies using ELISA. A questionnaire was used to collect management factors likely to be associated with Salmonella identification. Prevalence of Salmonella in each sample and its confidence interval was adjusted for clustering by herds using linearization technique. A generalized estimating equation was used to determine the odds ratio and significance level for each management factor in a logistic regression model. Salmonella was found in all 22 study pig herds with a fecal sample prevalence of 63% (95%CI: 56-69%) and a serum sample prevalence of 72%. However, isolation results were not significantly different from ELISA results. The most isolated serotype was Salmonella Rissen (49%) followed by Salmonella Typhimurium (19%), Salmonella Stanley (12%) and Salmonella Weltevreden (4%) being significantly different in the different specimens collected (p = .024). The final logistic regression model with isolation results as outcome showed that medium herd size (OR = 2.32, p = 0.003), quality certification according to the Department of Livestock Development standard (OR = 1.88, p = 0.000), use of effective microorganisms (OR = 1.51, p = 0.022), slurry waste management (OR = 2.17, p = 0.000) and less number of pigs per pen (OR = 1.12, p = 0.000) were significantly associated with positive Salmonella isolation; with positive ELISA results, however, only the use of effective microorganisms was significantly associated (OR = 2.63, p = 0.011). © 2008 Elsevier B.V. All rights reserved.